Francis Poictevin et sa vision de l’environnement : une approche écocritique des Paysages - Sasin, Eliza (Romanica Silesiana, 2024)
Francis Poictevin was a French author of decadent and symbolist inspiration. His poetic prose is diaristic and impressionistic, and draws richly on the natural world, which finds its particular realisation in Paysages (1888). Based on the guidelines of an ecologically engaged literary text as defined by Lawrence Buell, the current research aims to present the author’s vision of the environment and to answer the question of the autonomy of the nature depicted. The human-environmental relationship, the motive of the passage of time and the changeability of the seasons, as well as the eco-sensitivity of the author are taken into account. Poictevin, by giving his work the form of a collage, presents a natural world full of active actors, weighing up the ecosystem full of dependencies.